Management of Acceleration Models in SD Ar-Rafi' Bandung - Hidayat, Rizky Ramadhan (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2018)
his article explores the management of acceleration models in elementary schools. Education in Indonesia has not paid enough attention to education for children or students who are intellectually gifted. The classical class systems have been influenced by students who have different potential, so that students who have intellectual talent become undeveloped. Indonesia has around 1.3 million children who have the potential to be Special and Talent Special (CIBI) or often called 'gifted-talented'. Unfortunately, only 9,500 (0.7%) have received services in the form of acceleration programs. One of the elementary schools in Bandung that has held an acceleration program is SD Ar-Rafi'. هذه المقالة بخثت فى إدارة نموذج التسريع في المدرسة الابتدائية الرافع في باندونج. لم يعط التعليم في إندونيسيا الاهتمام الكافي للأطفال أو الطلاب الموهوبين فكريًا ، فالنظام الطبقي الكلاسيكي الذي يتم تشغيله يجمع بين الطلاب الذين لديهم إمكانات مختلفة لا يجعل الطلاب الذين لديهم موهبة فكرية يتطور. يوجد في إندونيسيا حوالي 1.3 مليون طفل في سن الدراسة ممن لديهم القدرة على أن يكونوا مواهب خاصة ومميزة (CIBI). ومع الأسف ، الذين يتلقون خدمات خاصة في شكل برامج التسيرع 9500 (0.7 ٪) من الأطفال فقط . واحدة من المدارس الابتدائية في مدينة باندونج التي عقدت برنامج التسريع هي المدرسة الابتدائية الرافع . Artikel ini membahas mengenai manajemen model percepatan di sekolah dasar di Sdar-Rafi’ Bandung. Pendidikan di Indonesia belum memberikan perhatian yang cukup pada pendidikan untuk anak-anak atau siswa yang berbakat secara intelektual. Sistem kelas klasikal yang telah berjalan memadukan siswa yang memiliki potensi berbeda sehingga siswa yang memiliki bakat intelektual menjadi tidak berkembang. Indonesia memiliki sekitar 1,3 juta anak usia sekolah yang berpotensi menjadi specially special dan talent special (CIBI) atau sering disebut 'gifted-talented'. Sayangnya, hanya 9.500 (0,7%) anak-anak telah menerima layanan khusus dalam bentuk program percepatan. Salah satu sekolah dasar di kota Bandung yang telah mengadakan program akselerasi adalah SD Ar-Rafi’.